Steel material for hot forming, hot forming member, and manufacturing method thereof
A specially formulated steel material with precise composition and processing steps addresses the challenges of achieving high strength and energy absorption in hot molding steel materials, resulting in improved tensile strength and uniformity.
Patent Information
- Application Number
- JP2022530941
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-17
- Filing Date
- 2020-12-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-12-18
AI Technical Summary
Hot molding steel materials used in automobile structural members face challenges in achieving high strength and energy absorption capabilities while maintaining uniform physical properties.
A steel material composition with specific ranges of C, Si, Mn, P, S, Al, Cr, Mo, and N, along with an alloy index of 7 or more, is developed. This material undergoes a manufacturing process involving heating, hot rolling, cooling, cold rolling, annealing, and aluminum-based plating to enhance strength and energy absorption.
The resulting hot molding steel material achieves a tensile strength of 1000 MPa or more, excellent collision energy absorption, and improved material uniformity, addressing the limitations of existing hot molding steel materials.
Smart Images

Figure 0007648620000005 
Figure 0007648620000006 
Figure 0007648620000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a hot-forming steel material, a hot-formed member, and a method for producing the same. [Background technology]
[0002] In recent years, hot-formed ultra-high strength members have been widely applied to structural members of automobiles for the purpose of improving fuel efficiency and protecting passengers by reducing the weight of the automobile. Patent Document 1 has been proposed as a representative technology related to such hot forming. Patent Document 1 proposes a technology in which an Al-Si plated steel sheet is heated to 850°C or higher, and then hot-formed by pressing and quenched to form the structure of the member into martensite, thereby ensuring ultra-high strength with a tensile strength exceeding 1600 MPa. In the case of the technology proposed in Patent Document 1, since forming is performed at high temperatures, complex shapes can be easily formed, and the increase in strength due to quenching in a mold can be expected to have a weight reduction effect due to the increased strength.
[0003] However, in the case of hot-formed parts manufactured by hot forming, the microstructure is made of martensite, and although it has high strength during a collision, it has poor bendability and is therefore limited in terms of energy absorption. Therefore, in order to compensate for the relatively poor energy absorption capacity, a technology has been proposed that incorporates a blank with a combination of different materials or different thicknesses (TWB, tailor welded blank) into hot forming, and various research projects are being conducted.
[0004] However, although low-strength hot forming steel materials with excellent energy absorption capacity have been developed and used as materials for TWB hot forming, in the case of regular hot forming steel materials for TWB, it is not easy to ensure uniform physical properties due to differences in cooling conditions at different positions in the actual part due to low hardening capacity, and the tensile strength is only at the level of 500 to 600 MPa, so there is a demand to achieve further weight reduction effects by improving strength. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] U.S. Patent No. 6,296,805 Summary of the Invention [Problem to be solved by the invention]
[0006] One aspect of the present invention is to provide a hot-forming steel material, a hot-formed member, and a manufacturing method thereof, which can impart high strength to a member while also imparting excellent collision energy absorption capacity.
[0007] The object of the present invention is not limited to the above. A person having ordinary skill in the art to which the present invention pertains will have no difficulty in understanding further object of the present invention from the overall matters in the specification of the present invention. [Means for solving the problem]
[0008] One embodiment of the present invention is a steel sheet comprising, by weight percent, 0.06-0.1% C, 0.05-0.6% Si, 0.6-2% Mn, 0.05% or less P, 0.02% or less S, 0.01-0.1% Al, 0.01-0.8% Cr, 0.5% or less (excluding 0%) Mo, 0.02% or less N, the balance being Fe and unavoidable impurities, and having an alloy factor represented by the following relational formula 1 of 7 or more, and containing 10 or more carbides having an equivalent circle diameter of 0.5 μm or more. 5 pieces / mm 2 The present invention provides a hot forming steel material which is:
[0009] [Equation 1] Alloy index=I(Mn)×I(Si)×I(Cr)×I(Mo) (In the above Relational Formula 1, the I value for each component is I(Mn) = 3.34 x Mn+1, I(Si) = 0.7 x Si+1, I(Cr) = 2.16 x Cr+1, and I(Mo) = 3 x Mo+1, and the content of each component is in weight percent.)
[0010] Another embodiment of the present invention is a steel sheet containing, by weight %, 0.06-0.1% C, 0.05-0.6% Si, 0.6-2% Mn, 0.05% or less P, 0.02% or less S, 0.01-0.1% Al, 0.01-0.8% Cr, 0.5% or less (excluding 0%) Mo, 0.02% or less N, the balance being Fe and unavoidable impurities, having an alloy factor represented by the following relational formula 1 of 7 or more, and having 10 or more carbides with a circle equivalent diameter of 0.5 μm or more. 4 pieces / mm 2 A hot-formed part is provided, which is
[0011] [Equation 1] Alloy index=I(Mn)×I(Si)×I(Cr)×I(Mo) (In the above Relational Formula 1, the I value for each component is I(Mn) = 3.34 x Mn+1, I(Si) = 0.7 x Si+1, I(Cr) = 2.16 x Cr+1, and I(Mo) = 3 x Mo+1, and the content of each component is in weight percent.)
[0012] Still another embodiment of the present invention is an alloy containing, by weight %, 0.06 to 0.1% C, 0.05 to 0.6% Si, 0.6 to 2% Mn, 0.05% or less P, 0.02% or less S, 0.01 to 0.1% Al, 0.01 to 0.8% Cr, 0.5% or less (excluding 0%) Mo, 0.02% or less N, the balance being Fe and unavoidable impurities, and an alloy index (alloy index) represented by the following relational formula 1. the step of heating a steel slab having a thermal expansion factor (TFA) of 7 or more at 1050 to 1300°C; finish hot rolling the heated steel slab at 800 to 950°C to obtain a hot-rolled steel sheet; coiling the hot-rolled steel sheet at 500 to 700°C; cooling the coiled hot-rolled steel sheet from a coiling temperature to 400°C at a cooling rate of 10°C / Hr or more; cold rolling the cooled hot-rolled steel sheet to obtain a cold-rolled steel sheet; heating the cold-rolled steel sheet at a rate of 20°C / s or less in a temperature range from 400°C to an annealing temperature; annealing the heated cold-rolled steel sheet at 740 to 860°C; and cooling the annealed cold-rolled steel sheet from the annealing temperature to 660°C at a cooling rate of 1°C / s or more.
[0013] [Equation 1] Alloy index=I(Mn)×I(Si)×I(Cr)×I(Mo) (In the above Relational Formula 1, the I value for each component is I(Mn) = 3.34 x Mn+1, I(Si) = 0.7 x Si+1, I(Cr) = 2.16 x Cr+1, and I(Mo) = 3 x Mo+1, and the content of each component is in weight percent.)
[0014] Yet another embodiment of the present invention provides a method for producing a hot-formed part, the method including the steps of obtaining a blank using the above-mentioned hot-forming steel material, heating the blank to Ac3 to 980°C and then holding the blank at Ac3 to 980°C for 1 to 1000 seconds, hot-forming the heated and held blank, and then cooling the blank to room temperature. Effect of the Invention
[0015] According to one aspect of the present invention, it is possible to provide a hot-forming steel material which has a high strength of at least 1000 MPa based on a tensile strength, while also having high collision energy absorption capacity and capable of producing components with excellent material uniformity, a hot-formed component using the same, and a manufacturing method for the same.
[0016] The various and beneficial advantages and effects of the present invention are not limited to the above, but can be more easily understood in the course of describing specific embodiments of the present invention. [Brief description of the drawings]
[0017] [Figure 1] 1 shows a simplified concept of CIE (Crack Initiation Energy), which is a criterion for evaluating the impact energy absorption capacity in the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a hot-formed part manufactured according to an embodiment of the present invention. [Diagram 3] 1 is a graph showing collision energy absorption capacity depending on carbon content and alloy index for Examples 1 to 7 and Comparative Examples 3 to 9 according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The terminology used herein is for the purpose of referring to particular embodiments only and is not intended to limit the present invention. As used herein, the singular forms "a," "an," and "the" include the plural forms unless the term clearly indicates to the contrary.
[0019] The meaning of "comprising" as used in the specification embodies the specified properties, regions, integers, steps, operations, elements, components and / or components, and does not exclude the presence or addition of other specified properties, regions, integers, steps, operations, elements, components and / or groups.
[0020] Unless otherwise defined, all terms, including technical and scientific terms, used herein have the same meaning as commonly understood by a person of ordinary skill in the art to which the present invention belongs. Terms defined in commonly used dictionaries are additionally interpreted as having a meaning consistent with the relevant technical literature and the presently disclosed content, and are not interpreted as ideal or very formal meanings unless defined.
[0021] The present inventors have conducted extensive research into methods for improving the impact energy absorption capacity of hot-formed components, and have evaluated the effects of various components, manufacturing conditions, structures, etc., using the energy (area under the load-displacement curve) up to the maximum load in a three-point bending test (VDA238-100) as an index that can adequately represent the impact energy absorption capacity of a hot-formed component.
[0022] As a result, it was concluded that in hot forming steel, the collision energy absorption capacity of the hot formed part can be maximized by controlling the range of carbon content, the hardening ability of alloy elements, the cooling conditions after hot rolling, the heating and cooling conditions during annealing, and the number density of coarse carbides present in the structure at certain levels, and the present invention was completed based on this conclusion.
[0023] Hereinafter, a hot forming steel material according to one aspect of the present invention will be described in detail. It should be noted that in the present invention, the content of each element is expressed in weight percent unless otherwise specified. The proportion of crystals and structures is based on the area unless otherwise specified.
[0024] First, the chemical composition of the steel material for hot forming according to one aspect of the present invention will be described. The steel material for hot forming according to the present invention contains, by weight, C: 0.06-0.1%, Si: 0.05-0.6%, Mn: 0.6-2%, P: 0.05% or less, S: 0.02% or less, Al: 0.01-0.1%, Cr: 0.01-0.8%, Mo: 0.01-0.5%, N: 0.02% or less, with the balance being Fe and inevitable impurities.
[0025] Carbon (C): 0.06~0.1% Carbon (C) is an essential element added to improve the strength of heat-treated members. In general, in ultra-high strength hot forming steel materials, the C content is generally high at 0.2% or more, but in order to achieve the maximum effect from the viewpoint of collision energy absorption capacity, an appropriate C content is necessary. If the C content is less than 0.06%, it is difficult to ensure sufficient strength, and ultimately, even if the bendability is high, the collision energy absorption capacity is rather reduced, so that 0.06% or more needs to be added. On the other hand, if the C content exceeds 0.1%, the strength is high, but the bendability is reduced and the collision energy absorption capacity is reduced, so it can be limited to 0.1% or less. Therefore, the C content is preferably in the range of 0.06 to 0.1%. The lower limit of the C content is more preferably 0.065%, and more preferably 0.07%. The upper limit of the C content is more preferably 0.095%, and more preferably 0.09%.
[0026] Silicon (Si): 0.05-0.6% Silicon (Si) is an element to be added as a deoxidizer in steelmaking, and is also a solid solution strengthening element that suppresses the generation of carbides, contributing to an increase in the strength of hot-formed members and is added as an element that is effective in homogenizing material properties. If the content is less than 0.05%, the above-mentioned effects cannot be expected. On the other hand, if the Si content exceeds 0.6%, the plating property is significantly reduced due to Si oxides generated on the surface of the steel sheet during annealing, so the addition can be limited to 0.6% or less. Therefore, the Si content is preferably in the range of 0.05 to 0.6%. The lower limit of the Si content is more preferably 0.1%, and even more preferably 0.15%. The upper limit of the Si content is more preferably 0.55%, and even more preferably 0.5%.
[0027] Manganese (Mn): 0.6-2% Manganese (Mn) is required to be added not only to ensure the effect of solid solution strengthening, but also to suppress the formation of ferrite during hot forming by improving hardening ability. If the Mn content is less than 0.6%, not only is there a limit to obtaining the above effect, but if the Mn content is too low, other expensive alloy elements are required excessively due to insufficient hardening ability, which may cause a problem of significantly increasing manufacturing costs. On the other hand, if the Mn content exceeds 2%, not only the cold rollability may decrease due to an increase in the strength of the steel sheet before the hot forming process, but also the band structure arranged in the rolling direction of the microstructure phase may deepen, resulting in poor collision energy absorption ability. Therefore, the Mn content is preferably in the range of 0.6 to 2%. The lower limit of the Mn content is more preferably 0.7%, more preferably 0.8%, and most preferably 0.9%. The upper limit of the Mn content is more preferably 1.8%, more preferably 1.6%, and most preferably 1.4%.
[0028] Phosphorus (P): 0.05% or less Phosphorus (P) exists in steel as an impurity, and if its content exceeds 0.05%, it may significantly embrittle the weldability of hot-formed parts. On the other hand, since the above-mentioned P is an impurity, its lower limit does not need to be particularly limited, but since controlling the P content to less than 0.001% may require high manufacturing costs, it may be limited to 0.001% or more.
[0029] Sulfur (S): 0.02% or less Sulfur (S) is present in steel as an impurity and is an element that impairs the ductility, impact properties, and weldability of hot-formed parts, so the maximum content can be limited to 0.02%. Meanwhile, since S is an impurity, the lower limit does not need to be particularly limited, but controlling the S content to less than 0.0001% may require high manufacturing costs, so the S content can be limited to 0.0001% or more.
[0030] Aluminum (Al): 0.01-0.1% Aluminum (Al), together with Si, is an element that acts as a deoxidizer in steelmaking to increase the cleanliness of steel. If the Al content is less than 0.01%, the above effect is difficult to obtain, and if the content exceeds 0.1%, there is a problem that the high-temperature ductility is reduced due to excess AlN formed during the continuous casting process, and slab cracks are likely to occur. Therefore, the Al content is preferably in the range of 0.01 to 0.1%. The lower limit of the Al content is more preferably 0.015%. The upper limit of the Al content is more preferably 0.08%, further preferably 0.07%, and most preferably 0.06%.
[0031] Chromium (Cr): 0.01-0.8% Chromium (Cr) is added to ensure the hardenability of steel, like Mn. If the Cr content is less than 0.01%, it may be difficult to ensure sufficient hardenability. On the other hand, if the Cr content exceeds 0.8%, the hardenability improvement effect is small compared to the amount added, and the content promotes the formation of coarse iron carbides, thereby deteriorating the impact energy absorption ability, so the upper limit can be limited to 0.8%. Therefore, the Cr content is preferably in the range of 0.01 to 0.8%. The lower limit of the Cr content is more preferably 0.015%, and even more preferably 0.02%. The upper limit of the Cr content is more preferably 0.75%, and even more preferably 0.7%.
[0032] Molybdenum (Mo): 0.5% or less (excluding 0%) Molybdenum (Mo) not only has the effect of improving the hardenability of steel like Cr and Mn, but also has the effect of increasing bendability by forming fine precipitates to refine crystal grains. However, if the Mo content exceeds 0.5%, the cost of the ferroalloy increases excessively compared to the effect, so the upper limit can be limited to 0.5%. Therefore, the Mo content is preferably in the range of 0.5% or less (excluding 0%). The Mo content is more preferably 0.45% or less, even more preferably 0.4% or less, and most preferably 0.35% or less.
[0033] Nitrogen (N): 0.02% or less The above-mentioned N is contained in the steel as an impurity. If the N content exceeds 0.02%, there is a problem that slab cracks are likely to occur due to the formation of AlN, as in the case of Al described above. On the other hand, since the above-mentioned N is an impurity, the lower limit does not need to be particularly limited, but since controlling the N content to less than 0.001% may require high manufacturing costs, it can be limited to 0.001% or more.
[0034] Meanwhile, the hot forming steel material according to one aspect of the present invention may further selectively contain one or more of Ni: 0.5% or less, Nb: 0.1% or less, Ti: 0.1% or less, and B: 0.01% or less in addition to the above-mentioned alloy components.
[0035] Nickel (Ni): 0.5% or less Nickel (Ni) is an austenite stabilizing element, and the addition of Ni can improve the hardenability of steel. However, since Ni is an expensive alloying element, it is preferable to set the upper limit at 0.5% in consideration of the increase in manufacturing costs relative to the effect of improving hardenability. Therefore, it is preferable that the Ni content is in the range of 0.5% or less. On the other hand, in order to fully obtain the effect of hardenability due to the addition of Ni, it is more preferable that the lower limit of the Ni content is 0.01%, further preferably 0.03%, and most preferably 0.05%. The upper limit of the Ni content is more preferably 0.45%, further preferably 0.4%, and most preferably 0.35%.
[0036] Niobium (Nb): 0.1% or less Niobium (Nb) is an element that can obtain a precipitation strengthening effect by forming fine precipitates, and can obtain the effect of increasing strength and improving bendability by refining crystal grains. In addition, it can suppress excessive crystal grain growth during heating for hot forming, thereby making the material robust against fluctuations in heat treatment conditions. However, if the Nb content exceeds 0.1%, not only will the effect saturate, but the increase in precipitation temperature may increase relatively coarse precipitates, which may reduce efficiency compared to costs. Therefore, the Nb content is preferably in the range of 0.1% or less. The lower limit of the Nb content is more preferably 0.005%, even more preferably 0.01%, and most preferably 0.015%. The upper limit of the Nb content is more preferably 0.09%, even more preferably 0.08%, and most preferably 0.07%.
[0037] Titanium (Ti): 0.1% or less Titanium (Ti) is an element that may be added when B is added to ensure hardening ability by combining with nitrogen remaining as an impurity in steel to form TiN. In addition, the formation of TiC precipitates can be expected to have precipitation strengthening and grain refinement effects. However, if the Ti content exceeds 0.1%, a large amount of coarse TiN is formed, which deteriorates the impact energy absorption ability, so the upper limit can be limited to 0.1%. Therefore, the Ti content is preferably in the range of 0.1% or less. The lower limit of the Ti content is more preferably 0.005%, even more preferably 0.01%, and most preferably 0.015%. The upper limit of the Ti content is more preferably 0.08%, even more preferably 0.06%, and most preferably 0.05%.
[0038] Boron (B): 0.01% or less Boron (B) is an element that can improve hardening ability even with a small amount of addition, and can segregate to the prior austenite grain boundaries to effectively suppress the embrittlement of hot-formed parts caused by the grain boundary segregation of P and / or S. However, if its content exceeds 0.01%, it can cause the following problems: 23 Since the formation of CB6 complex compounds causes brittleness during hot rolling, the upper limit can be limited to 0.01%. Therefore, the B content is preferably in the range of 0.01% or less. The lower limit of the B content is more preferably 0.0001%, further preferably 0.0003%, and most preferably 0.0005%. The upper limit of the B content is more preferably 0.009%, further preferably 0.007%, and most preferably 0.005%.
[0039] In addition to the above-mentioned steel composition, the remainder may include Fe and inevitable impurities. Inevitable impurities are those that may be mixed unintentionally in the normal steel manufacturing process, and cannot be completely excluded. Any engineer in the field of normal steel manufacturing can easily understand the meaning of this. In addition, the present invention does not completely exclude the addition of compositions other than the above-mentioned steel composition.
[0040] In the hot forming steel material according to one aspect of the present invention, in order to satisfy the above-mentioned composition system and maximize the collision energy absorption capacity and minimize the hardness deviation in the hot formed member, it is preferable that the alloy factor represented by the following relational expression 1 is controlled to 7 or more. If the alloy factor is less than 7, it is difficult to ensure sufficient hardening ability, and there is a possibility that a large hardness deviation occurs in the hot formed member. In addition, grain boundary ferrite is formed in the surface layer of the hot formed member, and there is a possibility that the collision energy absorption capacity is significantly deteriorated. The alloy factor is more preferably 7.5 or more, and even more preferably 8 or more. In the present invention, the effect to be obtained by the present invention can be secured even if the alloy factor is only 7 or more, so the upper limit is not particularly limited. However, for example, from the viewpoint of reducing manufacturing costs, the alloy factor may be 40 or less, more preferably 30 or less. Meanwhile, the following Relational Equation 1 is an equation derived by the present inventors through a linear regression analysis of the effect of each element on hardenability by a final hardness change test for each cooling rate after heating a number of ferroalloys having different contents of main alloying elements based on the same carbon content to an austenite region.
[0041] [Equation 1] Alloy index=I(Mn)×I(Si)×I(Cr)×I(Mo) (In the above Relational Formula 1, the I value for each component is I(Mn) = 3.34 x Mn+1, I(Si) = 0.7 x Si+1, I(Cr) = 2.16 x Cr+1, and I(Mo) = 3 x Mo+1, and the content of each component is in weight percent.)
[0042] In the case of hot forming steel used for TWB, energy absorption is one of the important properties, and this energy absorption is affected by strength and bending properties. That is, the higher the strength and the better the bending properties, the better the energy absorption. In general, the factor that has the greatest effect on the strength of hot forming steel after hot forming is the martensite fraction, and in particular, when martensite is the main structure, it is greatly affected by the carbon content. In addition, the bending properties vary somewhat depending on the structure, but generally, when it is composed of a single phase, it shows excellent properties, and when it is composed of two or more phases, it shows excellent properties as the strength difference between the phases is smaller. Considering these properties, in the region of carbon content less than 0.06%, not only is the strength low, but it is difficult to avoid the formation of soft ferrite during cooling, and rather, as the interphase strength of the final structure increases, the bending properties relative to the strength deteriorate, and the collision energy absorption ability decreases. On the other hand, in the region of C content exceeding 0.1%, a high-strength martensite single phase structure can be easily secured, but the bending properties decrease due to the increase in strength, and ultimately the collision energy absorption ability decreases. Even if the C content satisfies the range of the present invention, when the alloy index value is less than 7, the formation of soft phases such as ferrite during cooling is difficult to avoid due to insufficient hardenability, resulting in reduced bending properties and therefore reduced collision energy absorption. Therefore, in order to ensure a good level of collision energy absorption, both strength and bending properties must be considered.
[0043] The hot forming steel material according to one aspect of the present invention has 10 carbides having a circle equivalent diameter of 0.5 μm or more. 5 pieces / mm 2 The present inventors have concluded that in order to maximize the excellent collision energy absorption ability of hot-formed components, it is important to appropriately ensure the strength and bendability of the material, and have confirmed through various experiments that it is possible to ensure bendability by appropriately controlling the number density of coarse carbides from the steel plate. 5 pieces / mm 2If the number density of the coarse carbides exceeds 100%, even if some of the iron carbides are redissolved during heating for hot forming, the remaining part will remain in the member after hot forming. The coarse carbides that remain without being completely dissolved act as starting points for crack generation during bending deformation, which reduces the bendability and ultimately reduces the impact energy absorption ability. The lower the number density of the coarse carbides, the more advantageous it is, so the present invention does not particularly limit the lower limit.
[0044] The hot forming steel material according to one aspect of the present invention may include one or more of ferrite: 50 to 90 area %, pearlite: 30 area % or less, bainite: 20 area % or less, and martensite: 20 area % or less. The ferrite is a soft phase and is an effective structure for reducing the load in the blanking process of the steel sheet when making a blank, and in order to obtain the above effect, it is preferable to secure 50 area % or more. However, if it exceeds 90 area %, carbon may be excessively distributed in structures other than ferrite when making a blank, and carbon may be distributed unevenly even after hot forming. Therefore, the ferrite is preferably in the range of 50 to 90 area %. If the pearlite exceeds 30 area %, cementite may be incompletely dissolved after hot forming, reducing the strength or causing unevenness in the material. If the bainite and martensite each exceed 20 area %, the strength of the steel sheet may increase excessively, and problems such as die wear may occur when making a blank.
[0045] The steel material for hot forming according to one aspect of the present invention may have an aluminum-based plating layer formed on at least one surface. In the present invention, the aluminum-based plating layer is not particularly limited, but in one non-limiting embodiment, the aluminum-based plating layer may contain, by weight %, 6 to 12% Si, 1 to 4% Fe, and the balance Al and unavoidable impurities.
[0046] The hot-formed member according to one aspect of the present invention will be described in detail below. The hot-formed member according to one aspect of the present invention can be manufactured by hot press forming the above-mentioned hot forming steel material. The hot-formed member according to one aspect of the present invention preferably has the above-mentioned alloy composition and alloy index. In addition, the hot-formed member preferably has 10 carbides having a circle equivalent diameter of 0.5 μm or more. 4 pieces / mm 2 It is preferable that the number density and size of the carbides are less than 100%. Carbides that are present in the steel sheet before hot forming are dissolved in the steel during the heating stage for hot forming, so that the number density and size of the carbides are reduced compared to the state of the steel sheet before hot forming. However, coarse carbides above a certain size are not completely dissolved during the normal heating stage and remain in the hot formed component. Therefore, it is preferable that the number density and size of the carbides with a circle equivalent diameter of 0.5 μm or more are less than 100% in the hot formed component. 4 pieces / mm 2 If the bending deformation exceeds this limit, the coarse carbides may act as starting points for crack generation during bending deformation, as described above, possibly resulting in a deterioration in the impact energy absorption capacity.
[0047] In one aspect of the present invention, the hot-formed member may have a microstructure that is a martensite single-phase structure or a mixed structure that contains martensite and 40% or less by area of bainite. The martensite is an effective structure for ensuring the strength targeted by the present invention, and therefore the microstructure of the present invention may be a martensite single-phase structure. On the other hand, although bainite has a structure that is slightly weaker in strength than martensite, it does not significantly reduce bendability when formed in a martensite matrix, and is therefore advantageous for ensuring strength. Therefore, in the present invention, the microstructure may have a mixed structure that contains 40% or less by area of bainite together with the martensite. However, if the fraction of bainite is less than 40% by area, it may be difficult to ensure the strength targeted by the present invention.
[0048] Meanwhile, the microstructure may further include one or more of ferrite of 10 area % or less and retained austenite of 5 area % or less. The ferrite and retained austenite are structures that may be inevitably included in the manufacturing process. If the ferrite structure exceeds 10 area %, not only the strength may decrease but also the bending properties may be significantly deteriorated, and if the retained austenite structure exceeds 5 area %, the strength may decrease or the inflow of hydrogen from the atmospheric gas during hot forming may increase, increasing the possibility of hydrogen embrittlement.
[0049] The hot-formed member according to one aspect of the present invention may have a crack initiation energy (CIE) of 25,000 Nm or more when subjected to a three-point bending test according to the VDA standard (VDA238-100). Fig. 1 shows a simplified concept of CIE (Crack Initiation Energy), which is a criterion for evaluating the collision energy absorption capacity in the present invention.
[0050] In one aspect of the present invention, the hot-formed part may have a hardness deviation of 0.3 or less when the hardness is measured at any point of the hot-formed part, the difference between the maximum and minimum values is taken as the hardness deviation, and the hardness deviation is divided by the average hardness of the hot-formed part to give a deviation level. Meanwhile, the present invention is not particularly limited in the number of the any points, and the hardness can be measured at any 9 points, for example.
[0051] The hot-formed member according to one aspect of the present invention may have a yield strength (YS): 800 MPa or more, a tensile strength (TS): 1000 MPa or more, and an elongation (El): 5% or more.
[0052] In the following, a method for producing a steel bar for hot forming according to one aspect of the present invention will be described in detail. However, the method for producing described below is merely one embodiment among all possible embodiments, and does not necessarily mean that the steel bar for hot forming according to the present invention should be produced only by the method for producing described below.
[0053] First, a steel slab satisfying the above-mentioned alloy composition and alloy index is heated at 1050 to 1300 ° C. If the heating temperature of the steel slab is less than 1050 ° C, not only is it difficult to homogenize the structure of the slab, but also when using precipitated elements, it may be difficult to re-dissolve them. On the other hand, if the heating temperature exceeds 1300 ° C, an excessive oxide layer is formed, which may increase the possibility of inducing surface defects after hot rolling. Therefore, the heating temperature of the steel slab is preferably 1050 to 1300 ° C. The lower limit of the steel slab heating temperature is more preferably 1070 ° C, and more preferably 1100 ° C. The upper limit of the steel slab heating temperature is more preferably 1280 ° C, and more preferably 1250 ° C.
[0054] Thereafter, the heated steel slab is finish hot-rolled at 800 to 950°C to obtain a hot-rolled steel sheet. If the finish hot-rolling temperature is less than 800°C, a mixed grain structure occurs in the surface layer of the steel sheet due to two-phase rolling, and it may be difficult to control the sheet shape. On the other hand, if the finish hot-rolling temperature exceeds 950°C, there is a problem that the crystal grains are likely to become coarse due to hot rolling. Therefore, the finish hot-rolling temperature is preferably 800 to 950°C. The lower limit of the finish hot-rolling temperature is more preferably 810°C, and even more preferably 820°C. The upper limit of the finish hot-rolling temperature is more preferably 940°C, and even more preferably 930°C.
[0055] Thereafter, the hot-rolled steel sheet is coiled at 500 to 700°C. If the coiling temperature is less than 500°C, martensite is formed in the entire or part of the steel sheet, making it difficult to control the sheet shape, and the strength of the hot-rolled steel sheet increases, which may cause a problem of reduced rollability in the subsequent cold rolling process. On the other hand, if the coiling temperature exceeds 700°C, coarse carbides are formed, which may reduce the impact energy absorption ability of the hot-formed member. Therefore, the coiling temperature is preferably 500 to 700°C. The lower limit of the coiling temperature is more preferably 520°C, and more preferably 550°C. The upper limit of the coiling temperature is more preferably 680°C, and more preferably 650°C.
[0056] Thereafter, the coiled hot-rolled steel sheet is cooled from the coiling temperature to 400°C at a cooling rate of 10°C / Hr or more. If the cooling rate is less than 10°C / Hr, the time is sufficient for carbides to grow, and there is a possibility that a defect occurs in that a large number of coarse carbides are formed during the cooling of the hot-rolled coil. Therefore, the cooling rate is preferably 10°C / Hr or more. The cooling rate is more preferably 12°C / Hr or more, and even more preferably 15°C / Hr or more. On the other hand, in the present invention, the effect to be obtained by the present invention can be obtained even if the cooling rate is only 10°C / Hr or more, so the upper limit of the cooling rate is not particularly limited. However, for example, from the viewpoint of reducing costs due to capital investment, the cooling rate may be 500°C / Hr or less, more preferably 45°C / Hr or less, and even more preferably 400°C / Hr or less.
[0057] After the coiling and cooling, and before the cold rolling, the cooled hot-rolled steel sheet may be subjected to a step of pickling, which can remove scale formed on the surface of the steel sheet to improve the quality of the product surface.
[0058] Thereafter, the hot-rolled steel sheet is cold-rolled to obtain a cold-rolled steel sheet. In the present invention, the reduction ratio during the cold rolling is not particularly limited, but for example, a reduction ratio of 30 to 80% can be applied to obtain a target steel thickness.
[0059] On the other hand, according to one aspect of the present invention, the cold-rolled steel sheet may be subjected to continuous annealing and aluminum-based plating, or the cooled hot-rolled steel sheet may be subjected to aluminum-based plating immediately after pickling.
[0060] Thereafter, in order to anneal the cold-rolled steel sheet, it is preferable to heat the cold-rolled steel sheet at a temperature range from 400 ° C. to the annealing temperature at a rate of 20 ° C. / s or less. If the heating rate from 400 ° C. to the annealing temperature exceeds 20 ° C. / s, the time for the carbides precipitated at the hot rolling stage to be redissolved may be insufficient, and coarse carbides may remain, which may reduce the collision energy absorption ability of the finally obtained hot-formed part. Therefore, the heating rate from 400 ° C. to the annealing temperature is preferably 20 ° C. / s or less. The heating rate is more preferably 18 ° C. / s or less, and even more preferably 15 ° C. / s or less. On the other hand, in the present invention, the effect to be obtained by the present invention can be obtained even if the heating rate is only 20 ° C. / s or less, so the lower limit of the heating rate is not particularly limited. However, for example, in consideration of annealing productivity, the heating rate may be 0.5 ° C. / s or more, more preferably 1 ° C. / s or more, and even more preferably 1.5 ° C. / s or more. On the other hand, in the present invention, in the temperature range from the cold rolling temperature to less than 400° C., the heating rate is not particularly limited, because controlling the heating rate has little effect on the re-dissolution of carbides.
[0061] The heated cold-rolled steel sheet is preferably annealed at 740 to 860°C. If the annealing temperature is less than 740°C, the recrystallization of the cold-rolled structure is not sufficiently performed, resulting in a poor sheet shape, or the strength after plating may be excessively high, which may induce die wear during the blanking process. On the other hand, if the annealing temperature exceeds 860°C, there is a possibility that a problem occurs in which Si, Mn, etc. form surface oxides during the annealing process, resulting in a poor plating surface. Therefore, the annealing temperature is preferably 740 to 860°C. The lower limit of the annealing temperature is more preferably 750°C, and even more preferably 760°C. The upper limit of the annealing temperature is more preferably 850°C, and even more preferably 840°C.
[0062] On the other hand, the atmosphere during the continuous annealing is preferably a non-oxidizing atmosphere, and for example, a hydrogen-nitrogen mixed gas can be used. In this case, the dew point temperature of the atmospheric gas may be -70 to -30°C. In order to make the dew point temperature less than -70°C, additional equipment for control is required, which causes a problem of increased manufacturing costs. If the dew point exceeds -30°C, annealing oxides are excessively formed on the surface of the steel sheet during annealing, which may cause defects such as non-plating. Therefore, the dew point temperature of the atmospheric gas during the continuous annealing is preferably -70 to -30°C. The lower limit of the dew point temperature of the atmospheric gas is more preferably -65°C, and even more preferably -60°C. The upper limit of the dew point temperature of the atmospheric gas is more preferably -35°C, and even more preferably -40°C.
[0063] Thereafter, the annealed cold-rolled steel sheet is cooled from the annealing temperature to 660°C at a cooling rate of 1°C / s or more. 5 pieces / mm 2In order to achieve the above, it is preferable to set the cooling rate from the annealing temperature to 660 ° C. to 1 ° C. / s or more. If the cooling rate is less than 1 ° C. / s, a large amount of coarse carbides are formed, and the collision energy absorption capacity of the finally obtained hot-formed part may be reduced. Therefore, the cooling rate is preferably 1 ° C. / s or more. The cooling rate is more preferably 1.5 ° C. / s or more, and even more preferably 2 ° C. / s or more. On the other hand, in the present invention, the effect to be obtained by the present invention can be obtained even if the cooling rate is only 1 ° C. / s or more, so the upper limit of the cooling rate is not particularly limited. However, for example, from the viewpoint of suppressing defects in the steel sheet shape, the cooling rate may be 50 ° C. / s or less, more preferably 45 ° C. / s or less, and even more preferably 40 ° C. / s or less.
[0064] After the step of cooling the annealed cold-rolled steel sheet, the method may further include a step of immersing the cooled cold-rolled steel sheet in an Al-based plating bath to form an aluminum-based plating layer. In the present invention, the composition of the Al-based plating bath and plating conditions are not particularly limited. However, as a non-limiting example, the composition of the plating bath may include Si: 6 to 12%, Fe: 1 to 4%, the balance Al and other inevitable impurities, and the plating amount is 30 to 130 g / m2 on one side, which is commonly applied in the technical field. 2 In the composition of the above-mentioned coating bath, if the Si content is less than 6%, there is a drawback that the temperature of the coating bath rises excessively, causing deterioration of the equipment, and if it exceeds 12%, there is a drawback that the alloying is excessively delayed, and the heating time for hot forming must be extended. If the Fe content is less than 1%, there is a possibility that the coating adhesion and spot weldability will decrease, and if it exceeds 4%, there is a possibility that excessive dross will be generated in the coating bath, causing poor surface quality. The coating weight is 30 g / m on one side basis. 2 If the thickness is less than 130 g / m, it may be difficult to ensure the desired corrosion resistance of the hot-formed parts. 2 If the coating weight exceeds this range, not only will the manufacturing cost increase due to the excessive coating weight, but it may not be easy to coat the steel sheet with a uniform coating weight in the entire coil width and length directions.
[0065] Hereinafter, a method for producing a hot-formed part according to one aspect of the present invention will be described in detail. However, the method for producing the hot-formed part according to the present invention is merely one embodiment among all possible embodiments, and does not necessarily mean that the hot-formed part according to the present invention should be produced only by the method for producing the hot-formed part according to the present invention.
[0066] First, a hot forming steel material manufactured by the above-mentioned manufacturing method is prepared, and a blank for hot forming is manufactured using the hot forming steel material. Then, the blank is heated at a temperature above the austenite single phase region temperature, more specifically, in a temperature range of Ac3 temperature or higher and 980°C or lower. If the blank heating temperature is lower than Ac3 temperature, untransformed ferrite is present, so it may be difficult to ensure a predetermined strength. On the other hand, if the heating temperature exceeds 980°C, excessive oxides are generated on the surface of the member, so it may be difficult to ensure spot weldability. Therefore, the blank heating temperature is preferably Ac3 to 980°C. The lower limit of the blank heating temperature is more preferably Ac3 + 5°C, and even more preferably Ac3 + 10°C. The upper limit of the blank heating temperature is more preferably 970°C, and even more preferably 960°C.
[0067] The heated blank is preferably held in the above temperature range for 1 to 1000 seconds. If the holding time is less than 1 second, the temperature is not uniformed throughout the blank, which may induce material differences depending on the location, and if the holding time exceeds 1000 seconds, excessive oxides are generated on the surface of the member, as in the case of an excessively high heating temperature, which may make it difficult to ensure spot weldability. Therefore, the holding time is preferably 1 to 1000 seconds. The lower limit of the holding time is more preferably 30 seconds, and even more preferably 60 seconds. The upper limit of the holding time is more preferably 900 seconds, and even more preferably 800 seconds.
[0068] The heated and held blank is then hot-formed and cooled to room temperature to finally produce a hot-formed part. In the present invention, the specific conditions for the hot-forming are not particularly limited, and a hot-forming method commonly known in the technical field to which the present invention pertains can be directly applied. EXAMPLES
[0069] The present invention will be described in more detail below through examples. However, it should be noted that the following examples are intended to illustrate and embody the present invention, and are not intended to limit the scope of the present invention. This is because the scope of the present invention is determined by the matters described in the claims and matters that can be reasonably inferred therefrom.
[0070] (Example) A steel slab having a thickness of 40 mm and having an alloy composition as shown in Table 1 below was produced by vacuum melting. The steel slab was heated to 1250°C, and then hot-rolled to a finish hot rolling temperature of 900°C to obtain a hot-rolled steel sheet. Thereafter, the coiling temperature and the cooling rate from the coiling temperature to 400°C were applied to each steel type using a replica heat treatment furnace under the conditions as shown in Table 2 below, and hot rolling was performed so that all the final hot-rolled thicknesses were 3 mm. Thereafter, the hot-rolled steel sheet was pickled, and then cold-rolled with a cold reduction of 50% to obtain a cold-rolled steel sheet. Thereafter, the cold-rolled steel sheet was heated under the conditions as shown in Table 2 below at a controlled heating rate from 400°C to the annealing temperature, annealed in a 5% hydrogen-95% nitrogen atmosphere, and then the cooling rate from the annealing temperature to 660°C was controlled to produce a cold-rolled steel sheet. Thereafter, the cold-rolled steel sheet was cooled and then subjected to Al-based plating. At this time, the composition of the Al-based plating bath is Al-9%Si-2%Fe with the remainder consisting of unavoidable impurities, and the plating weight is 80g / m on one side. 2The steel sheet thus manufactured was prepared as a blank, and then hot-formed using a hot-forming die to manufacture a hot-formed member having the form shown in FIG. 2. At this time, the heating temperature of the blank was 900° C., the holding time was 6 minutes, and the conveying time from the heating furnace to forming was all 10 seconds, which was applied in the same manner. The number of carbides having a circle equivalent diameter of 0.5 μm or more was measured for the cold-rolled steel sheet manufactured as described above, and the results are shown in Table 2 below. The number of carbides having a circle equivalent diameter of 0.5 μm or more, the microstructure, and the mechanical properties of the hot-formed member manufactured as described above were measured, and the results are shown in Tables 3 and 4 below.
[0071] The number of carbides having a circle equivalent diameter of 0.5 μm or more was measured by preparing a thin foil specimen and observing 10 fields of view at a magnification of 10,000 times using a transmission electron microscope (TEM).
[0072] The microstructure was measured using a scanning electron microscope after etching the surface of the steel sheet with Nital.
[0073] The yield strength (YS), tensile strength (TS) and elongation (El) were measured by taking ASTM standard test pieces in a direction parallel to the rolling direction of the steel plate and then conducting a tensile test.
[0074] The impact energy absorption capacity was evaluated by conducting a three-point bending test in accordance with the VDA standard (VDA238-100), and then measuring the area from the load-displacement curve obtained to the maximum load (CIE: Crack initiation Energy). Values higher than 25,000 Nm, the CIE value of ordinary 1,500 MPa-class hot forming steel, were rated as "good", and values below this were rated as "poor".
[0075] In addition, to confirm the uniformity of the physical properties of the hot-formed parts, three test pieces were taken from each of the top, left side, and right side of the formed part, and hardness measurements were performed using a Vickers hardness tester. The average hardness, hardness deviation (difference between the maximum and minimum values of the hardness measured at nine points) and deviation level (hardness deviation / average hardness) were then measured, and the physical property uniformity was rated as "good" when the deviation level was 0.3 or less, and "poor" when it exceeded that level.
[0076] [Table 1]
[0077] [Table 2]
[0078] [Table 3]
[0079] [Table 4]
[0080] As can be seen from Tables 1 to 4 above, in the case of Examples 1 to 7, which satisfy all of the alloy compositions, alloy indices, and manufacturing conditions proposed by the present invention, it can be confirmed that the collision energy absorption capacity is good and the physical properties within the component are uniform.
[0081] In the case of Comparative Examples 1 and 2, the alloy composition and alloy index satisfy the ranges of the present invention, but the manufacturing conditions of the coiling temperature, the cooling rate after coiling, and the heating rate during annealing are outside the ranges of the present invention, and as a result, the number density of coarse carbides increases, and the collision energy absorption capacity of the finally obtained hot-formed part is poor.
[0082] In Comparative Examples 3 to 5, the alloy composition of the steel plate is met, but the alloy index does not meet the conditions of the present invention. It can be seen that excessive hardness deviation occurs due to insufficient hardening ability, and the uniformity of physical properties within the component is poor.
[0083] Comparative Examples 6 to 8 are cases in which the C content exceeds the conditions of the present invention. Although there is an effect of increasing the strength due to the increased C content, it is clear that the bendability is significantly reduced compared to the increase in strength, and the collision energy absorption ability is rather inferior.
[0084] Comparative Example 9 is a case where the C content does not satisfy the conditions of the present invention, and not only was the target strength not ensured, but it was also found that the collision energy absorption capacity was reduced as a result.
[0085] Fig. 3 is a graph showing the collision energy absorption capacity according to the carbon content and alloy index of Examples 1 to 7 and Comparative Examples 3 to 9. As shown in Fig. 3, the C content and alloy index are directly related to the collision energy absorption capacity of the hot-formed member, and it can be seen that good collision energy absorption capacity can be ensured only when the C content and alloy index proposed by the present invention are satisfied.
Claims
1. The alloy contains, by weight, C: 0.06-0.1%, Si: 0.05-0.6%, Mn: 0.6-2%, P: 0.05% or less, S: 0.02% or less, Al: 0.01-0.1%, Cr: 0.01-0.8%, Mo: 0.5% or less (excluding 0%), N: 0.02% or less, with the balance being Fe and unavoidable impurities; The alloy factor represented by the following formula 1 is 7 or more, 10 carbides with a circle equivalent diameter of 0.5 μm or more 5 pieces / mm 2 The following is a hot forming steel sheet. [Relationship 1] Alloy index = I (Mn) x I (Si) x I (Cr) x I (Mo) (In the above Relational Formula 1, the I value for each component is I(Mn) = 3.34 x Mn + 1, I(Si) = 0.7 x Si + 1, I(Cr) = 2.16 x Cr + 1, I(Mo) = 3 x Mo + 1, and the content of each component is in weight percent.)
2. The steel plate for hot forming according to claim 1, further comprising one or more of Ni: 0.5% or less, Nb: 0.1% or less, Ti: 0.1% or less, and B: 0.01% or less.
3. The steel sheet for hot forming according to claim 1 or 2, wherein the steel sheet has an aluminum-based plating layer formed on at least one surface thereof.
4. The steel sheet for hot forming according to claim 3, wherein the aluminum-based plating layer contains, by weight%, Si: 6 to 12%, Fe: 1 to 4%, the balance Al and inevitable impurities.
5. The alloy contains, by weight, C: 0.06-0.1%, Si: 0.05-0.6%, Mn: 0.6-2%, P: 0.05% or less, S: 0.02% or less, Al: 0.01-0.1%, Cr: 0.01-0.8%, Mo: 0.5% or less (excluding 0%), N: 0.02% or less, with the balance being Fe and unavoidable impurities; The alloy factor represented by the following formula 1 is 7 or more, 10 carbides with a circle equivalent diameter of 0.5 μm or more 4 pieces / mm 2 is as follows: A hot-formed member having a microstructure which is a martensite single-phase structure or a mixed structure containing 40 area % or less of bainite (including 0 area %) and the remainder martensite, and further containing one or more of 10 area % or less (including 0 area %) of ferrite and 5 area % or less (including 0 area %) of retained austenite. [Relationship 1] Alloy index = I (Mn) x I (Si) x I (Cr) x I (Mo) (In the above Relational Formula 1, the I value for each component is I(Mn) = 3.34 x Mn + 1, I(Si) = 0.7 x Si + 1, I(Cr) = 2.16 x Cr + 1, I(Mo) = 3 x Mo + 1, and the content of each component is in weight percent.)
6. 6. The hot formed member of claim 5, wherein the microstructure further comprises one or more of up to 10 area percent ferrite and up to 5 area percent retained austenite.
7. The member according to claim 5 or 6, wherein when a three-point bending test is performed according to the VDA standard (VDA238-100), the area from the load-displacement curve obtained in the three-point bending test to the maximum load (CIE: Crack initiation Energy) is 25000 Nm or more.
8. 8. The hot formed part of claim 5, wherein the part has a hardness deviation level of 0.3 or less. (Note that the hardness deviation level is a value obtained by dividing the hardness deviation by the average hardness value of the hot-formed part, and the hardness deviation means the difference between the maximum and minimum values obtained by measuring the hardness at any point.)
9. The hot formed member according to any one of claims 5 to 8, wherein the member has a yield strength (YS): 800 MPa or more, a tensile strength (TS): 1000 MPa or more, and an elongation (El): 5% or more.
10. The steel slab contains, by weight, C: 0.06-0.1%, Si: 0.05-0.6%, Mn: 0.6-2%, P: 0.05% or less, S: 0.02% or less, Al: 0.01-0.1%, Cr: 0.01-0.8%, Mo: 0.5% or less (excluding 0%), N: 0.02% or less, the balance being Fe and unavoidable impurities, and has an alloy factor of 7 or more represented by the following relational formula 1, and is heated at 1050-1300°C; Finish hot rolling the heated steel slab at 800 to 950° C. to obtain a hot-rolled steel sheet; coiling the hot-rolled steel sheet at 500 to 700 ° C.; cooling the coiled hot-rolled steel sheet from a coiling temperature to 400° C. at a cooling rate of 10° C. / Hr or more; cold rolling the cooled hot-rolled steel sheet to obtain a cold-rolled steel sheet; Heating the cold-rolled steel sheet at a temperature range of 400° C. to an annealing temperature at a rate of 20° C. / s or less; annealing the heated cold-rolled steel sheet at 740 to 860°C; The method for producing a steel sheet for hot forming according to any one of claims 1 to 4, comprising: cooling the annealed cold-rolled steel sheet from the annealing temperature to 660°C at a cooling rate of 1°C / s or more. [Relationship 1] Alloy index = I (Mn) x I (Si) x I (Cr) x I (Mo) (In the above Relational Formula 1, the I value for each component is I(Mn) = 3.34 x Mn + 1, I(Si) = 0.7 x Si + 1, I(Cr) = 2.16 x Cr + 1, I(Mo) = 3 x Mo + 1, and the content of each component is in weight percent.)
11. The method for producing a steel sheet for hot forming according to claim 10, further comprising pickling the cooled hot-rolled steel sheet before the cold rolling.
12. The method for producing a steel sheet for hot forming according to claim 10 or 11, wherein the rolling reduction rate during the cold rolling is 30 to 80%.
13. The method for producing a steel sheet for hot forming according to any one of claims 10 to 12, wherein a dew point temperature (Dew point) of the atmospheric gas during the annealing is −70 to −30 ° C.
14. The method for producing a steel sheet for hot forming according to any one of claims 10 to 13, further comprising, after the step of cooling the annealed cold-rolled steel sheet, immersing the cooled cold-rolled steel sheet in an Al-based plating bath to form an aluminum-based plating layer.
15. The method for producing a steel sheet for hot forming according to claim 14, wherein the Al-based plating bath contains, by weight%, Si: 6 to 12%, Fe: 1 to 4%, the balance Al and inevitable impurities.
16. When the plating layer is formed, the plating coating weight is 30 to 130 g / m on one side. 2 The method for producing a steel sheet for hot forming according to claim 14 or 15,
17. Obtaining a blank using the hot forming steel sheet according to any one of claims 1 to 4; heating the blank to Ac3 to 980° C. and then holding it for 1 to 1000 seconds; and cooling the heated and held blank to room temperature after hot forming the blank.
Citation Information
Patent Citations
Hot press method for high strength automotive member made of cold rolled or hot rolled steel sheet, or al-based plated or zn-based plated steel sheet, and hot pressed parts
JP2006051543A
Method for producing a component by hot forming a pre-product made of steel
US20160130675A1
Coated hot- and cold-rolled steel sheet comprising a very high resistance after thermal treatment
US6296805B1
Hot stamp molded article, method for producing hot stamp molded article, energy absorbing member, and method for producing energy absorbing member
WO2012157581A1
Cold-rolled steel sheet and method for producing cold-rolled steel sheet
WO2013105638A1